2023
DOI: 10.1007/s10787-023-01261-6
|View full text |Cite
|
Sign up to set email alerts
|

Mito-TEMPO mitigates 5-fluorouracil-induced intestinal injury via attenuating mitochondrial oxidative stress, inflammation, and apoptosis: an in vivo study

Abstract: Background Recent evidences highlight role of mitochondria in the development of 5-fluorouracil (5-FU)-induced intestinal toxicity. Mitochondria-targeted antioxidants are well-known for their protective effects in mitochondrial oxidative stress- mediated diseases. In the present study, we investigated protective effect of Mito-TEMPO in 5-FU-induced intestinal toxicity. Methods Mito-TEMPO (0.1 mg/kg b.w.) was administered intraperitoneally to male BALB/c mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…5). Notably, a recent study suggested that mitochondrial stress, which is triggered upon 5FU treatment in vitro and in vivo [62][63][64] , leads to increased ZNF598 stability in a K63-linked ubiquitination dependent manner 65 . However, it is not clear how mitochondrial stress and/or mTOR activation could lead to ZNF598 or GIGYF2 deubiquitination and stabilisation upon acute 5FU treatment.…”
Section: Discussionmentioning
confidence: 99%
“…5). Notably, a recent study suggested that mitochondrial stress, which is triggered upon 5FU treatment in vitro and in vivo [62][63][64] , leads to increased ZNF598 stability in a K63-linked ubiquitination dependent manner 65 . However, it is not clear how mitochondrial stress and/or mTOR activation could lead to ZNF598 or GIGYF2 deubiquitination and stabilisation upon acute 5FU treatment.…”
Section: Discussionmentioning
confidence: 99%